Social difference and constitutionalism in Pan-Asia (Comparative constitutional law and policy, 2014)
"One of the most vexing problems in the theory and practice of politics is the issue of difference. How do we build a just and stable polity in the face of identity differences that have historically been the basis for inequality, injustice, and violence? Such differences can take a variety of forms, including religious difference, race and ethnicity, language difference, urban/rural tensions, and gender. In many countries, divisions such as these are the fault lines that threaten the stability of the social and legal order. This book addresses the role of constitutions and constitutionalism in dealing with the challenge of difference. In the spring of 2011, a conference held at Indiana University brought together a distinguished group of lawyers, political scientists, historians, religious studies scholars, and area studies experts to consider how constitutions and constitutionalism address issues of difference across a wide swath of the world we called "Pan-Asia." Pan-Asia runs from the Middle East, through Central Asia, South Asia, Southeast Asia, East Asia, and into Oceania. This is a meta-region across which ideas and influences have traveled for centuries. It is also an area of the world that includes every type of difference in abundant supply. Pan-Asia, therefore, provides a wonderful laboratory for examining the role of constitutions in addressing difference. The existing literatures, while rich in other ways, do not speak directly to this issue of constitutions as a mechanism for addressing difference. There is a vast political theory literature on the relationship between democracy and difference"--Provided by publisher.